Authoritarianism and civil society in Asia - Spires, Anthony J. 1970-; Ogawa, Akihiro 1968- (Routledge, Taylor & Francis Group, 2023)
"This book represents a pioneering interdisciplinary effort to analyse Asian civil society under authoritarianism, a regime type that is re-appearing or deepening after several decades of increased political liberalisation. By organising its approach into four main themes, this volume succinctly reveals the challenges facing civil society in authoritarian regimes, including: actions under political repression; transitions to democracy; uncivil society; political capture and legal control. It features in-depth analyses of a variety of Asian nations, from 'hard' authoritarian regimes, like China, to 'electoral' authoritarian regimes, like Cambodia whilst also addressing countries experiencing democratic regression, such as the Philippines. By highlighting concrete responses and initiatives taken by civil society under authoritarianism, it advances the intellectual mandate of redefining Asia as a dynamic and interconnected formation and, moreover, as a space for the production of new theoretical insight. Contributing to our understanding of the tensions, dynamics, and potentialities that animate state-society relations in authoritarian regimes, this will be essential reading for students and scholars of civil society, authoritarianism, and Asian politics more generally"--
Keywords: Geschichte; Zivilgesellschaft; Autoritärer Staat; Asien; Civil society / Asia; Authoritarianism / Asia; Asia / Politics and government; Authoritarianism; Civil society; Politics and government; Asia; Aufsatzsammlung